POLIOMYELITIS: A REVIEW - Tayyab, Muhammad; Anwar, Muhammad Saeed; Hashmi, Inam Qadir Javed (Journal of Ayub Medical College Abbottabad, 2000)
Poliomyelitis presents as acute febrile illness with sudden onset of weakness of extremities. It is caused by type 1,2, and 3 poliovirus and spreads most commonly by faecal-oral route, particularly in areas with poor sanitation.1’2 It is primarily a disease of children, 70-90% of the cases occur in those less than 3 years of age. 3 The disease is preventable through improved sanitation, hygiene and immunization with polio vaccines. In May 1988, World Health Assembly (WHA) declared that World Health Organization (WHO) was committed to the global eradication of poliomyelitis by the year 2000.4 Substantial progress towards the global eradication of poliomyelitis by the year 2000 has been achieved since May 1988. Today the world stands on the brink of achievement of goal of global poliomyelitis eradication, under the leadership of WHO